Progress and challenges in the synthesis of sequence controlled polysaccharides - Fittolani, Giulio; Tyrikos-Ergas, Theodore; Vargová, Denisa; Chaube, Manishkumar A.; Delbianco, Martina (Beilstein Journal of Organic Chemistry, 2021)
The sequence, length and substitution of a polysaccharide influence its physical and biological properties. Thus, sequence controlled polysaccharides are important targets to establish structure–properties correlations. Polymerization techniques and enzymatic methods have been optimized to obtain samples with well-defined substitution patterns and narrow molecular weight distribution. Chemical synthesis has granted access to polysaccharides with full control over the length. Here, we review the progress towards the synthesis of well-defined polysaccharides. For each class of polysaccharides, we discuss the available synthetic approaches and their current limitations.
Keywords: enzymes; glycans; polysaccharides; synthesis; well-defined polymers

Essentials of Glycobiology - Varki, A.; Cummings, R. D.; Esko, J. D.; Stanley, P.; Hart, G. W.; Aebi, M.; Darvill, A. G.; Kinoshita, T.; Packer, N. H.; Prestegard, J. H.; Schnaar, R. L.; Seeberger, P. H. (Cold Spring Harbor Laboratory Press, 2017)

(untitled) - de Moura, F. A.; Macagnan, F. T.; da Silva, L. P. (Int. J. Food Sci. Technol., 2015)

(untitled) - Verendel, J. J.; Church, T. L.; Andersson, P. G. (Synthesis, 2011)

(untitled) - Guerrini, M.; Beccati, D.; Shriver, Z.; Naggi, A.; Viswanathan, K.; Bisio, A.; Capila, I.; Lansing, J. C.; Guglieri, S.; Fraser, B.; Al-Hakim, A.; Gunay, N. S.; et al. (Nat. Biotechnol., 2008)

(untitled) - Anggara, K.; Zhu, Y.; Delbianco, M.; Rauschenbach, S.; Abb, S.; Seeberger, P. H.; Kern, K. (J. Am. Chem. Soc., 2020)

(untitled) - Wu, X.; Delbianco, M.; Anggara, K.; Michnowicz, T.; Pardo-Vargas, A.; Bharate, P.; Sen, S.; Pristl, M.; Rauschenbach, S.; Schlickum, U.; Abb, S.; Seeberger, P. H.; et al. (Nature, 2020)

(untitled) - Senf, D.; Ruprecht, C.; Kishani, S.; Matic, A.; Toriz, G.; Gatenholm, P.; Wågberg, L.; Pfrengle, F. (Angew. Chem., Int. Ed., 2018)

(untitled) - Kittle, J. D.; Qian, C.; Edgar, E.; Roman, M.; Esker, A. R. (ACS Omega, 2018)

(untitled) - Zhang, Q.; Gimeno, A.; Santana, D.; Wang, Z.; Valdés-Balbin, Y.; Rodríguez-Noda, L. M.; Hansen, T.; Kong, L.; Shen, M.; Overkleeft, H. S.; Vérez-Bencomo, V.; van der Marel, G. A.; et al. (ACS Cent. Sci., 2019)

(untitled) - Armstrong, Z.; Withers, S. G. (Biopolymers, 2013)

(untitled) - Smith, P. J.; Ortiz-Soto, M. E.; Roth, C.; Barnes, W. J.; Seibel, J.; Urbanowicz, B. R.; Pfrengle, F. (ACS Sustainable Chem. Eng., 2020)

(untitled) - Perugino, G.; Cobucci-Ponzano, B.; Rossi, M.; Moracci, M. (Adv. Synth. Catal., 2005)

Enzymatic Polymerization towards Green Polymer Chemistry - Kobayashi, S.; Uyama, H.; Kadokawa, J. (Springer International Publishing, 2019)

(untitled) - Faijes, M.; Planas, A. (Carbohydr. Res., 2007)

(untitled) - Shoda, S.-i.; Uyama, H.; Kadokawa, J.-i.; Kimura, S.; Kobayashi, S. (Chem. Rev., 2016)

(untitled) - Kobayashi, S.; Makino, A. (Chem. Rev., 2009)

(untitled) - Kadokawa, J.-i. (Chem. Rev., 2011)

(untitled) - Xiao, R.; Grinstaff, M. W. (Prog. Polym. Sci., 2017)

(untitled) - Mackenzie, L. F.; Wang, Q.; Warren, R. A. J.; Withers, S. G. (J. Am. Chem. Soc., 1998)

(untitled) - Danby, P. M.; Withers, S. G. (ACS Chem. Biol., 2016)

(untitled) - Hayes, M.; Pietruszka, J. (Molecules, 2017)

(untitled) - Cobucci-Ponzano, B.; Moracci, M. (Nat. Prod. Rep., 2012)

(untitled) - Wang, L.-X.; Huang, W. (Curr. Opin. Chem. Biol., 2009)

(untitled) - Adelwöhrer, C.; Takano, T.; Nakatsubo, F.; Rosenau, T. (Biomacromolecules, 2009)

(untitled) - Tokatly, A. I.; Vinnitskiy, D. Z.; Ustuzhanina, N. E.; Nifantiev, N. E. (Russ. J. Bioorg. Chem., 2021)

(untitled) - Kaeothip, S.; Demchenko, A. V. (Carbohydr. Res., 2011)

(untitled) - Jeanneret, R. A.; Johnson, S. E.; Galan, M. C. (J. Org. Chem., 2020)

(untitled) - Pardo-Vargas, A.; Delbianco, M.; Seeberger, P. H. (Curr. Opin. Chem. Biol., 2018)

(untitled) - Panza, M.; Pistorio, S. G.; Stine, K. J.; Demchenko, A. V. (Chem. Rev., 2018)

(untitled) - Hsu, C.-H.; Hung, S.-C.; Wu, C.-Y.; Wong, C.-H. (Angew. Chem., Int. Ed., 2011)

(untitled) - Panza, M.; Stine, K. J.; Demchenko, A. V. (Chem. Commun., 2020)

(untitled) - Seeberger, P. H. (Acc. Chem. Res., 2015)

(untitled) - Chang, C.-W.; Lin, M.-H.; Chan, C.-K.; Su, K.-Y.; Wu, C.-H.; Lo, W.-C.; Lam, S.; Cheng, Y.-T.; Liao, P.-H.; Wong, C.-H.; Wang, C.-C. (Angew. Chem., Int. Ed., 2021)

(untitled) - van der Vorm, S.; Hansen, T.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Chem. Sci., 2017)

(untitled) - Crich, D. (J. Am. Chem. Soc., 2021)

Reactivity Tuning in Oligosaccharide Assembly - Fraser-Reid, B.; Cristóbal López, J. (Springer, 2011)

(untitled) - Hettikankanamalage, A. A.; Lassfolk, R.; Ekholm, F. S.; Leino, R.; Crich, D. (Chem. Rev., 2020)

(untitled) - Matsuzaki, Y.; Ito, Y.; Nakahara, Y.; Ogawa, T. (Tetrahedron Lett., 1993)

(untitled) - Petitou, M.; Duchaussoy, P.; Driguez, P.-A.; Hérault, J.-P.; Lormeau, J.-C.; Herbert, J.-M. (Bioorg. Med. Chem. Lett., 1999)

(untitled) - Pozsgay, V. (Tetrahedron: Asymmetry, 2000)

(untitled) - Varki, A.; Cummings, R. D.; Aebi, M.; Packer, N. H.; Seeberger, P. H.; Esko, J. D.; Stanley, P.; Hart, G.; Darvill, A.; Kinoshita, T.; Prestegard, J. J.; Schnaar, R. L.; et al. (Glycobiology, 2015)

Cellulose Chemistry and Properties: Fibers, Nanocelluloses and Advanced Materials - Rojas, O. J. (Springer International Publishing, 2016)

(untitled) - O’Sullivan, A. C. (Cellulose, 1997)

(untitled) - Atalla, R. H. (Science, 1998)

(untitled) - Delmer, D. P. (Annu. Rev. Plant Physiol. Plant Mol. Biol., 1999)

(untitled) - Brown, R. M., Jr (J. Macromol. Sci., Part A: Pure Appl. Chem., 1996)

(untitled) - Rajinipriya, M.; Nagalakshmaiah, M.; Robert, M.; Elkoun, S. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Klemm, D.; Kramer, F.; Moritz, S.; Lindström, T.; Ankerfors, M.; Gray, D.; Dorris, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Habibi, Y.; Lucia, L. A.; Rojas, O. J. (Chem. Rev., 2010)

(untitled) - Moon, R. J.; Martini, A.; Nairn, J.; Simonsen, J.; Youngblood, J. (Chem. Soc. Rev., 2011)

(untitled) - Thomas, B.; Raj, M. C.; B, A. K.; H, R. M.; Joy, J.; Moores, A.; Drisko, G. L.; Sanchez, C. (Chem. Rev., 2018)

(untitled) - Schurz, J. (Prog. Polym. Sci., 1999)

(untitled) - Li, T.; Chen, C.; Brozena, A. H.; Zhu, J. Y.; Xu, L.; Driemeier, C.; Dai, J.; Rojas, O. J.; Isogai, A.; Wågberg, L.; Hu, L. (Nature, 2021)

(untitled) - Serizawa, T.; Fukaya, Y.; Sawada, T. (Polym. J., 2018)

(untitled) - Burchard, W. (Cellulose, 2003)

(untitled) - Potthast, A.; Rosenau, T.; Buchner, R.; Röder, T.; Ebner, G.; Bruglachner, H.; Sixta, H.; Kosma, P. (Cellulose, 2002)

(untitled) - Kostag, M.; Gericke, M.; Heinze, T.; El Seoud, O. A. (Cellulose, 2019)

(untitled) - Kobayashi, S. (J. Polym. Sci., Part A: Polym. Chem., 2005)

(untitled) - Billès, E.; Coma, V.; Peruch, F.; Grelier, S. (Polym. Int., 2017)

(untitled) - Nidetzky, B.; Zhong, C. (Biotechnol. Adv., 2020)

(untitled) - Kobayashi, S.; Kashiwa, K.; Kawasaki, T.; Shoda, S.-i. (J. Am. Chem. Soc., 1991)

(untitled) - Hiraishi, M.; Igarashi, K.; Kimura, S.; Wada, M.; Kitaoka, M.; Samejima, M. (Carbohydr. Res., 2009)

(untitled) - Hattori, T.; Ogata, M.; Kameshima, Y.; Totani, K.; Nikaido, M.; Nakamura, T.; Koshino, H.; Usui, T. (Carbohydr. Res., 2012)

(untitled) - Lee, J. H.; Brown, R. M.; Kuga, S.; Shoda, S.-i.; Kobayashi, S. (Proc. Natl. Acad. Sci. U. S. A., 1994)

(untitled) - Pylkkänen, R.; Mohammadi, P.; Arola, S.; de Ruijter, J. C.; Sunagawa, N.; Igarashi, K.; Penttilä, M. (Biomacromolecules, 2020)

(untitled) - Hata, Y.; Sawada, T.; Marubayashi, H.; Nojima, S.; Serizawa, T. (Langmuir, 2019)

(untitled) - Yataka, Y.; Sawada, T.; Serizawa, T. (Langmuir, 2016)

(untitled) - Serizawa, T.; Fukaya, Y.; Sawada, T. (Langmuir, 2017)

(untitled) - Hata, Y.; Kojima, T.; Koizumi, T.; Okura, H.; Sakai, T.; Sawada, T.; Serizawa, T. (ACS Macro Lett., 2017)

(untitled) - Hashimoto, T.; Tanaka, H.; Koizumi, S.; Kurosaki, K.; Ohmae, M.; Kobayashi, S. (Biomacromolecules, 2006)

(untitled) - Tanaka, H.; Koizumi, S.; Hashimoto, T.; Kurosaki, K.; Kobayashi, S. (Macromolecules, 2007)

(untitled) - Egusa, S.; Kitaoka, T.; Goto, M.; Wariishi, H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Egusa, S.; Kitaoka, T.; Igarashi, K.; Samejima, M.; Goto, M.; Wariishi, H. (J. Mol. Catal. B: Enzym., 2010)

(untitled) - Egusa, S.; Goto, M.; Kitaoka, T. (Biomacromolecules, 2012)

(untitled) - Nakamura, I.; Makino, A.; Sugiyama, J.; Ohmae, M.; Kimura, S. (Int. J. Biol. Macromol., 2008)

(untitled) - Nakamura, I.; Makino, A.; Horikawa, Y.; Sugiyama, J.; Ohmae, M.; Kimura, S. (Chem. Commun., 2011)

(untitled) - Nakamura, I.; Horikawa, Y.; Makino, A.; Sugiyama, J.; Kimura, S. (Biomacromolecules, 2011)

(untitled) - Andrade, P.; Muñoz‐García, J. C.; Pergolizzi, G.; Gabrielli, V.; Nepogodiev, S. A.; Iuga, D.; Fábián, L.; Nigmatullin, R.; Johns, M. A.; Harniman, R.; Eichhorn, S. J.; Angulo, J.; et al. (Chem. – Eur. J., 2021)

(untitled) - Serizawa, T.; Kato, M.; Okura, H.; Sawada, T.; Wada, M. (Polym. J., 2016)

(untitled) - Fujita, M.; Shoda, S.-i.; Kobayashi, S. (J. Am. Chem. Soc., 1998)

(untitled) - Kobayashi, S.; Makino, A.; Matsumoto, H.; Kunii, S.; Ohmae, M.; Kiyosada, T.; Makiguchi, K.; Matsumoto, A.; Horie, M.; Shoda, S.-I. (Biomacromolecules, 2006)

(untitled) - Codera, V.; Edgar, K. J.; Faijes, M.; Planas, A. (Biomacromolecules, 2016)

(untitled) - Nakatsubo, F.; Kamitakahara, H.; Hori, M. (J. Am. Chem. Soc., 1996)

(untitled) - Kamitakahara, H.; Hori, M.; Nakatsubo, F. (Macromolecules, 1996)

(untitled) - Hori, M.; Nakatsubo, F. (Macromolecules, 2001)

(untitled) - Yagura, T.; Ikegami, W.; Kamitakahara, H.; Takano, T. (Cellulose, 2020)

(untitled) - Kamitakahara, H.; Funakoshi, T.; Nakai, S.; Takano, T.; Nakatsubo, F. (Cellulose, 2009)

(untitled) - Kamitakahara, H.; Funakoshi, T.; Takano, T.; Nakatsubo, F. (Cellulose, 2009)

(untitled) - Sakakibara, K.; Takano, T.; Nakatsubo, F. (Cellulose, 2011)

(untitled) - Karakawa, M.; Kamitakahara, H.; Takano, T.; Nakatsubo, F. (Biomacromolecules, 2002)

(untitled) - Nishimura, T.; Nakatsubo, F. (Cellulose, 1997)

(untitled) - Nishimura, T.; Nakatsubo, F. (Tetrahedron Lett., 1996)

(untitled) - Yu, Y.; Tyrikos‐Ergas, T.; Zhu, Y.; Fittolani, G.; Bordoni, V.; Singhal, A.; Fair, R. J.; Grafmüller, A.; Seeberger, P. H.; Delbianco, M. (Angew. Chem., Int. Ed., 2019)

(untitled) - Murty, K. V. S. N.; Xie, T.; Bernet, B.; Vasella, A. (Helv. Chim. Acta, 2006)

(untitled) - Hayashi, T.; Marsden, M. P. F.; Delmer, D. P. (Plant Physiol., 1987)

(untitled) - Kuki, H.; Yokoyama, R.; Kuroha, T.; Nishitani, K. (Plants, 2020)

(untitled) - Culbertson, A. T.; Ehrlich, J. J.; Choe, J.-Y.; Honzatko, R. B.; Zabotina, O. A. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - Urbanowicz, B. R.; Bharadwaj, V. S.; Alahuhta, M.; Peña, M. J.; Lunin, V. V.; Bomble, Y. J.; Wang, S.; Yang, J.-Y.; Tuomivaara, S. T.; Himmel, M. E.; Moremen, K. W.; York, W. S.; et al. (Plant J., 2017)

(untitled) - Kinnaert, C.; Daugaard, M.; Nami, F.; Clausen, M. H. (Chem. Rev., 2017)

(untitled) - Fry, S. C.; York, W. S.; Albersheim, P.; Darvill, A.; Hayashi, T.; Joseleau, J.-P.; Kato, Y.; Lorences, E. P.; Maclachlan, G. A.; McNeil, M.; Mort, A. J.; Grant Reid, J. S.; et al. (Physiol. Plant., 1993)

(untitled) - Sakai, K.; Nakahara, Y.; Ogawa, T. (Tetrahedron Lett., 1990)

(untitled) - Bartetzko, M. P.; Pfrengle, F. (ChemBioChem, 2019)

(untitled) - Dallabernardina, P.; Schuhmacher, F.; Seeberger, P. H.; Pfrengle, F. (Org. Biomol. Chem., 2016)

(untitled) - Dallabernardina, P.; Ruprecht, C.; Smith, P. J.; Hahn, M. G.; Urbanowicz, B. R.; Pfrengle, F. (Org. Biomol. Chem., 2017)

(untitled) - Fauré, R.; Saura-Valls, M.; Brumer, H.; Planas, A.; Cottaz, S.; Driguez, H. (J. Org. Chem., 2006)

(untitled) - Fauré, R.; Cavalier, D.; Keegstra, K.; Cottaz, S.; Driguez, H. (Eur. J. Org. Chem., 2007)

(untitled) - Piens, K.; Henriksson, A.-M.; Gullfot, F.; Lopez, M.; Fauré, R.; Ibatullin, F. M.; Teeri, T. T.; Driguez, H.; Brumer, H. (Org. Biomol. Chem., 2007)

(untitled) - Lopez, M.; Fort, S.; Bizot, H.; Buléon, A.; Driguez, H. (Carbohydr. Polym., 2012)

(untitled) - Gullfot, F.; Ibatullin, F. M.; Sundqvist, G.; Davies, G. J.; Brumer, H. (Biomacromolecules, 2009)

(untitled) - Spadiut, O.; Ibatullin, F. M.; Peart, J.; Gullfot, F.; Martinez-Fleites, C.; Ruda, M.; Xu, C.; Sundqvist, G.; Davies, G. J.; Brumer, H. (J. Am. Chem. Soc., 2011)

(untitled) - Descroix, K.; Ferrieres, V.; Jamois, F.; Yvin, J.-C.; Plusquellec, D. (Mini-Rev. Med. Chem., 2006)

(untitled) - Ogawa, Y.; Noda, K.; Kimura, S.; Kitaoka, M.; Wada, M. (Int. J. Biol. Macromol., 2014)

(untitled) - Elsaidi, H. R. H.; Paszkiewicz, E.; Bundle, D. R. (Carbohydr. Res., 2015)

(untitled) - Adamo, R.; Hu, Q.-Y.; Torosantucci, A.; Crotti, S.; Brogioni, G.; Allan, M.; Chiani, P.; Bromuro, C.; Quinn, D.; Tontini, M.; Berti, F. (Chem. Sci., 2014)

(untitled) - Adamo, R.; Tontini, M.; Brogioni, G.; Romano, M. R.; Costantini, G.; Danieli, E.; Proietti, D.; Berti, F.; Costantino, P. (J. Carbohydr. Chem., 2011)

(untitled) - Huang, G.-L.; Mei, X.-Y.; Liu, M.-X. (Carbohydr. Res., 2005)

(untitled) - Huang, G.-L.; Mei, X.-Y.; Liu, M.-X.; Liu, T.-C. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Le Mai Hoang, K.; Pardo-Vargas, A.; Zhu, Y.; Yu, Y.; Loria, M.; Delbianco, M.; Seeberger, P. H. (J. Am. Chem. Soc., 2019)

(untitled) - Yashunsky, D. V.; Tsvetkov, Y. E.; Nifantiev, N. E. (Carbohydr. Res., 2016)

(untitled) - Yang, G.; Kong, F. (Carbohydr. Res., 2005)

(untitled) - Zhao, W.; Yang, G.; Kong, F. (Carbohydr. Res., 2003)

(untitled) - Zeng, Y.; Kong, F. (Carbohydr. Res., 2003)

(untitled) - Tanaka, H.; Amaya, T.; Takahashi, T. (Tetrahedron Lett., 2003)

(untitled) - Yang, G.; Kong, F. (Synlett, 2000)

(untitled) - Egusa, K.; Kusumoto, S.; Fukase, K. (Eur. J. Org. Chem., 2003)

(untitled) - Yashunsky, D. V.; Tsvetkov, Y. E.; Grachev, A. A.; Chizhov, A. O.; Nifantiev, N. E. (Carbohydr. Res., 2016)

(untitled) - Yang, F.; He, H.; Du, Y.; Lü, M. (Carbohydr. Res., 2002)

(untitled) - Ning, J.; Zhang, W.; Yi, Y.; Yang, G.; Wu, Z.; Yi, J.; Kong, F. (Bioorg. Med. Chem., 2003)

(untitled) - Zeng, Y.; Ning, J.; Kong, F. (Tetrahedron Lett., 2002)

(untitled) - Yu, H.; Williams, D. L.; Ensley, H. E. (Tetrahedron Lett., 2005)

(untitled) - He, H.; Yang, F.; Du, Y. (Carbohydr. Res., 2002)

(untitled) - Takeo, K.; Maki, K.; Wada, Y.; Kitamura, S. (Carbohydr. Res., 1993)

(untitled) - Jamois, F.; Ferrières, V.; Guégan, J.-P.; Yvin, J.-C.; Plusquellec, D.; Vetvicka, V. (Glycobiology, 2005)

(untitled) - Mo, K.-F.; Li, H.; Mague, J. T.; Ensley, H. E. (Carbohydr. Res., 2009)

(untitled) - Liao, G.; Zhou, Z.; Burgula, S.; Liao, J.; Yuan, C.; Wu, Q.; Guo, Z. (Bioconjugate Chem., 2015)

(untitled) - Liao, G.; Burgula, S.; Zhou, Z.; Guo, Z. (Eur. J. Org. Chem., 2015)

(untitled) - Tanaka, H.; Kawai, T.; Adachi, Y.; Hanashima, S.; Yamaguchi, Y.; Ohno, N.; Takahashi, T. (Bioorg. Med. Chem., 2012)

(untitled) - Tanaka, H.; Kawai, T.; Adachi, Y.; Ohno, N.; Takahashi, T. (Chem. Commun., 2010)

(untitled) - Hamagami, H.; Adachi, Y.; Ohno, N.; Tanaka, H. (Asian J. Org. Chem., 2019)

(untitled) - Weishaupt, M. W.; Hahm, H. S.; Geissner, A.; Seeberger, P. H. (Chem. Commun., 2017)

(untitled) - Weishaupt, M. W.; Matthies, S.; Seeberger, P. H. (Chem. – Eur. J., 2013)

(untitled) - Plante, O. J.; Palmacci, E. R.; Seeberger, P. H. (Science, 2001)

(untitled) - Dallabernardina, P.; Schuhmacher, F.; Seeberger, P. H.; Pfrengle, F. (Chem. – Eur. J., 2017)

(untitled) - Fairweather, J. K.; Hrmova, M.; Rutten, S. J.; Fincher, G. B.; Driguez, H. (Chem. – Eur. J., 2003)

(untitled) - Montel, E.; Hrmova, M.; Fincher, G. B.; Driguez, H.; Cottaz, S. (Aust. J. Chem., 2009)

(untitled) - Hrmova, M.; Imai, T.; Rutten, S. J.; Fairweather, J. K.; Pelosi, L.; Bulone, V.; Driguez, H.; Fincher, G. B. (J. Biol. Chem., 2002)

(untitled) - Pérez, X.; Faijes, M.; Planas, A. (Biomacromolecules, 2011)

(untitled) - Yashunsky, D. V.; Karelin, A. A.; Tsvetkov, Y. E.; Nifantiev, N. E. (Carbohydr. Res., 2018)

(untitled) - Wang, H.-R.; Li, Z.-L.; Ning, J.; Kong, F.-Z. (Chin. J. Chem., 2003)

(untitled) - Sittel, I.; Tran, A.-T.; Benito-Alifonso, D.; Galan, M. C. (Chem. Commun., 2013)

(untitled) - Manmode, S.; Kato, M.; Ichiyanagi, T.; Nokami, T.; Itoh, T. (Asian J. Org. Chem., 2018)

(untitled) - Smith, R.; Müller-Bunz, H.; Zhu, X. (Org. Lett., 2016)

(untitled) - Pistorio, S. G.; Nigudkar, S. S.; Stine, K. J.; Demchenko, A. V. (J. Org. Chem., 2016)

(untitled) - Huang, X.; Huang, L.; Wang, H.; Ye, X.-S. (Angew. Chem., Int. Ed., 2004)

(untitled) - Hashihayata, T.; Ikegai, K.; Takeuchi, K.; Jona, H.; Mukaiyama, T. (Bull. Chem. Soc. Jpn., 2003)

(untitled) - Yu, Y.; Gim, S.; Kim, D.; Arnon, Z. A.; Gazit, E.; Seeberger, P. H.; Delbianco, M. (J. Am. Chem. Soc., 2019)

(untitled) - Delbianco, M.; Kononov, A.; Poveda, A.; Yu, Y.; Diercks, T.; Jiménez-Barbero, J.; Seeberger, P. H. (J. Am. Chem. Soc., 2018)

(untitled) - Yi, Y.; Zhou, Z.; Ning, J.; Kong, F.; Li, J. (Synthesis, 2003)

(untitled) - Tanaka, H.; Adachi, M.; Tsukamoto, H.; Ikeda, T.; Yamada, H.; Takahashi, T. (Org. Lett., 2002)

(untitled) - Nicolaou, K. C.; Winssinger, N.; Pastor, J.; DeRoose, F. (J. Am. Chem. Soc., 1997)

(untitled) - Yamada, H.; Harada, T.; Takahashi, T. (J. Am. Chem. Soc., 1994)

(untitled) - Fügedi, P.; Birberg, W.; Garegg, P. J.; Pilotti, Å. (Carbohydr. Res., 1987)

(untitled) - Ossowski, P.; Pilotti, A.; Garegg, P. J.; Lindberg, B. (J. Biol. Chem., 1984)

(untitled) - Ossowski, P.; Pilotti, Å.; Garegg, P. J.; Lindberg, B. (Angew. Chem., Int. Ed. Engl., 1983)

(untitled) - Ning, J.; Yi, Y.; Kong, F. (Tetrahedron Lett., 2002)

(untitled) - Nicolaou, K. C.; Watanabe, N.; Li, J.; Pastor, J.; Winssinger, N. (Angew. Chem., Int. Ed., 1998)

(untitled) - Nigudkar, S. S.; Demchenko, A. V. (Chem. Sci., 2015)

(untitled) - Geoghegan, I.; Steinberg, G.; Gurr, S. (Trends Microbiol., 2017)

(untitled) - Komarova, B. S.; Orekhova, M. V.; Tsvetkov, Y. E.; Beau, R.; Aimanianda, V.; Latgé, J.-P.; Nifantiev, N. E. (Chem. – Eur. J., 2015)

(untitled) - Komarova, B. S.; Tsvetkov, Y. E.; Nifantiev, N. E. (Chem. Rec., 2016)

(untitled) - Hahm, H. S.; Hurevich, M.; Seeberger, P. H. (Nat. Commun., 2016)

(untitled) - Hirooka, M.; Koto, S. (Bull. Chem. Soc. Jpn., 1998)

(untitled) - Lam, S. N.; Gervay-Hague, J. (Carbohydr. Res., 2002)

(untitled) - Boltje, T. J.; Kim, J.-H.; Park, J.; Boons, G.-J. (Nat. Chem., 2010)

(untitled) - Tomita, S.; Tanaka, M.; Inoue, M.; Inaba, K.; Takahashi, D.; Toshima, K. (J. Org. Chem., 2020)

(untitled) - Tanaka, M.; Nakagawa, A.; Nishi, N.; Iijima, K.; Sawa, R.; Takahashi, D.; Toshima, K. (J. Am. Chem. Soc., 2018)

(untitled) - Yasomanee, J. P.; Demchenko, A. V. (Angew. Chem., Int. Ed., 2014)

(untitled) - Wang, L.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (J. Am. Chem. Soc., 2018)

(untitled) - Wang, L.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Eur. J. Org. Chem., 2019)

(untitled) - Wang, L.; Berni, F.; Enotarpi, J.; Overkleeft, H. S.; van der Marel, G.; Codée, J. D. C. (Org. Biomol. Chem., 2020)

(untitled) - Zhang, Y.; He, H.; Chen, Z.; Huang, Y.; Xiang, G.; Li, P.; Yang, X.; Lu, G.; Xiao, G. (Angew. Chem., Int. Ed., 2021)

(untitled) - Zhu, Y.; Delbianco, M.; Seeberger, P. H. (J. Am. Chem. Soc., 2021)

(untitled) - Meppen, M.; Wang, Y.; Cheon, H.-S.; Kishi, Y. (J. Org. Chem., 2007)

(untitled) - Cheon, H.-S.; Lian, Y.; Kishi, Y. (Org. Lett., 2007)

(untitled) - Ohdan, K.; Fujii, K.; Yanase, M.; Takaha, T.; Kuriki, T. (Biocatal. Biotransform., 2006)

(untitled) - Nishimura, T.; Akiyoshi, K. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2017)

(untitled) - Meng, X.; Pijning, T.; Dobruchowska, J. M.; Yin, H.; Gerwig, G. J.; Dijkhuizen, L. (Sci. Rep., 2016)

(untitled) - Meng, X.; Dobruchowska, J. M.; Gerwig, G. J.; Kamerling, J. P.; Dijkhuizen, L. (Carbohydr. Res., 2015)

(untitled) - Timell, T. E. (Adv. Carbohydr. Chem., 1964)

(untitled) - Thorsheim, K.; Siegbahn, A.; Johnsson, R. E.; Stålbrand, H.; Manner, S.; Widmalm, G.; Ellervik, U. (Carbohydr. Res., 2015)

(untitled) - Ebringerová, A.; Heinze, T. (Macromol. Rapid Commun., 2000)

(untitled) - Busse-Wicher, M.; Grantham, N. J.; Lyczakowski, J. J.; Nikolovski, N.; Dupree, P. (Biochem. Soc. Trans., 2016)

(untitled) - Grantham, N. J.; Wurman-Rodrich, J.; Terrett, O. M.; Lyczakowski, J. J.; Stott, K.; Iuga, D.; Simmons, T. J.; Durand-Tardif, M.; Brown, S. P.; Dupree, R.; Busse-Wicher, M.; Dupree, P. (Nat. Plants (London, U. K.), 2017)

(untitled) - Santibáñez, L.; Henríquez, C.; Corro-Tejeda, R.; Bernal, S.; Armijo, B.; Salazar, O. (Carbohydr. Polym., 2021)

(untitled) - Köhnke, T.; Östlund, Å.; Brelid, H. (Biomacromolecules, 2011)

(untitled) - Bosmans, T. J.; Stépán, A. M.; Toriz, G.; Renneckar, S.; Karabulut, E.; Wågberg, L.; Gatenholm, P. (Biomacromolecules, 2014)

(untitled) - Linder, Å.; Bergman, R.; Bodin, A.; Gatenholm, P. (Langmuir, 2003)

(untitled) - Timell, T. E. (J. Am. Chem. Soc., 1959)

(untitled) - Uryu, T.; Koyama, Y.; Matsuzaki, K. (J. Polym. Sci., Polym. Lett. Ed., 1979)

(untitled) - Uryu, T.; Koyama, Y.; Matsuzaki, K. (Makromol. Chem., 1984)

(untitled) - Uryu, T.; Yamanouchi, J.; Hayashi, S.; Tamaki, H.; Matsuzaki, K. (Macromolecules, 1983)

(untitled) - Kim, Y.-W.; Fox, D. T.; Hekmat, O.; Kantner, T.; McIntosh, L. P.; Warren, R. A. J.; Withers, S. G. (Org. Biomol. Chem., 2006)

(untitled) - Kobayashi, S.; Wen, X.; Shoda, S.-i. (Macromolecules, 1996)

(untitled) - Ben-David, A.; Bravman, T.; Balazs, Y. S.; Czjzek, M.; Schomburg, D.; Shoham, G.; Shoham, Y. (ChemBioChem, 2007)

(untitled) - Takeo, K.; Ohguchi, Y.; Hasegawa, R.; Kitamura, S. (Carbohydr. Res., 1995)

(untitled) - Chen, L.; Kong, F. (Carbohydr. Res., 2002)

(untitled) - Schmidt, D.; Schuhmacher, F.; Geissner, A.; Seeberger, P. H.; Pfrengle, F. (Chem. – Eur. J., 2015)

(untitled) - Senf, D.; Ruprecht, C.; de Kruijff, G. H. M.; Simonetti, S. O.; Schuhmacher, F.; Seeberger, P. H.; Pfrengle, F. (Chem. – Eur. J., 2017)

(untitled) - Khoushab, F.; Yamabhai, M. (Mar. Drugs, 2010)

(untitled) - Kurita, K. (Mar. Biotechnol., 2006)

(untitled) - Rinaudo, M. (Prog. Polym. Sci., 2006)

(untitled) - Azuma, K.; Izumi, R.; Osaki, T.; Ifuku, S.; Morimoto, M.; Saimoto, H.; Minami, S.; Okamoto, Y. (J. Funct. Biomater., 2015)

(untitled) - Xu, H.; Shen, B.; Qiao, M.; Linhardt, R. J.; Zhang, X. (Carbohydr. Polym., 2021)

(untitled) - Shoueir, K. R.; El-Desouky, N.; Rashad, M. M.; Ahmed, M. K.; Janowska, I.; El-Kemary, M. (Int. J. Biol. Macromol., 2021)

(untitled) - Bonin, M.; Sreekumar, S.; Cord-Landwehr, S.; Moerschbacher, B. M. (Int. J. Mol. Sci., 2020)

(untitled) - Naqvi, S.; Moerschbacher, B. M. (Crit. Rev. Biotechnol., 2017)

(untitled) - Yang, Y.; Yu, B. (Tetrahedron, 2014)

(untitled) - Wattjes, J.; Sreekumar, S.; Richter, C.; Cord-Landwehr, S.; Singh, R.; El Gueddari, N. E.; Moerschbacher, B. M. (React. Funct. Polym., 2020)

(untitled) - Cord-Landwehr, S.; Richter, C.; Wattjes, J.; Sreekumar, S.; Singh, R.; Basa, S.; El Gueddari, N. E.; Moerschbacher, B. M. (React. Funct. Polym., 2020)

(untitled) - Fuchs, K.; Cardona Gloria, Y.; Wolz, O.-O.; Herster, F.; Sharma, L.; Dillen, C. A.; Täumer, C.; Dickhöfer, S.; Bittner, Z.; Dang, T.-M.; Singh, A.; Haischer, D.; et al. (EMBO Rep., 2018)

(untitled) - Basa, S.; Nampally, M.; Honorato, T.; Das, S. N.; Podile, A. R.; El Gueddari, N. E.; Moerschbacher, B. M. (J. Am. Chem. Soc., 2020)

(untitled) - Osorio-Madrazo, A.; David, L.; Trombotto, S.; Lucas, J.-M.; Peniche-Covas, C.; Domard, A. (Biomacromolecules, 2010)

(untitled) - Einbu, A.; Grasdalen, H.; Vårum, K. M. (Carbohydr. Res., 2007)

(untitled) - Einbu, A.; Vårum, K. M. (Biomacromolecules, 2007)

(untitled) - Vårum, K. (Carbohydr. Polym., 2001)

(untitled) - Tømmeraas, K.; Vårum, K. M.; Christensen, B. E.; Smidsrød, O. (Carbohydr. Res., 2001)

(untitled) - Defaye, J.; Gadelle, A.; Pedersen, C. (Carbohydr. Res., 1994)

(untitled) - Capon, B.; Foster, R. L. (J. Chem. Soc. C, 1970)

(untitled) - Kidibule, P. E.; Santos-Moriano, P.; Jiménez-Ortega, E.; Ramírez-Escudero, M.; Limón, M. C.; Remacha, M.; Plou, F. J.; Sanz-Aparicio, J.; Fernández-Lobato, M. (Microb. Cell Fact., 2018)

(untitled) - Vaaje-Kolstad, G.; Horn, S. J.; Sørlie, M.; Eijsink, V. G. H. (FEBS J., 2013)

(untitled) - Horn, S. J.; Sorbotten, A.; Synstad, B.; Sikorski, P.; Sorlie, M.; Varum, K. M.; Eijsink, V. G. H. (FEBS J., 2006)

(untitled) - Aam, B. B.; Heggset, E. B.; Norberg, A. L.; Sørlie, M.; Vårum, K. M.; Eijsink, V. G. H. (Mar. Drugs, 2010)

(untitled) - Nishimura, S.-I.; Kuzuhara, H.; Takiguchi, Y.; Shimahara, K. (Carbohydr. Res., 1989)

(untitled) - Inaba, T.; OhgushiI, T.; Iga, Y.; Hasegawa, E. (Chem. Pharm. Bull., 1984)

(untitled) - Barker, S. A.; Foster, A. B.; Stacey, M.; Webber, J. M. (J. Chem. Soc., 1958)

(untitled) - Despras, G.; Alix, A.; Urban, D.; Vauzeilles, B.; Beau, J.-M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Alsina, C.; Faijes, M.; Planas, A. (Carbohydr. Res., 2019)

(untitled) - Makino, A.; Ohmae, M.; Kobayashi, S. (Macromol. Biosci., 2006)

(untitled) - Sakamoto, J.; Sugiyama, J.; Kimura, S.; Imai, T.; Itoh, T.; Watanabe, T.; Kobayashi, S. (Macromolecules, 2000)

(untitled) - Hashimoto, H.; Abe, Y.; Horito, S.; Yoshimura, J. (J. Carbohydr. Chem., 1989)

(untitled) - Crout, D. H. G.; Vic, G. (Curr. Opin. Chem. Biol., 1998)

(untitled) - Singh, S.; Gallagher, R.; Derrick, P. J.; Crout, D. H. G. (Tetrahedron: Asymmetry, 1995)

(untitled) - Akiyama, K.; Kawazu, K.; Kobayashi, A. (Carbohydr. Res., 1995)

(untitled) - Purushotham, P.; Podile, A. R. (J. Bacteriol., 2012)

(untitled) - Madhuprakash, J.; Tanneeru, K.; Purushotham, P.; Guruprasad, L.; Podile, A. R. (J. Biol. Chem., 2012)

(untitled) - Usui, T.; Matsui, H.; Isobe, K. (Carbohydr. Res., 1990)

(untitled) - Ohnuma, T.; Tanaka, T.; Urasaki, A.; Dozen, S.; Fukamizo, T. (J. Biochem., 2019)

(untitled) - Sirimontree, P.; Suginta, W.; Sritho, N.; Kanda, Y.; Shinya, S.; Ohnuma, T.; Fukamizo, T. (Biosci., Biotechnol., Biochem., 2014)

(untitled) - Ohnuma, T.; Fukuda, T.; Dozen, S.; Honda, Y.; Kitaoka, M.; Fukamizo, T. (Biochem. J., 2012)

(untitled) - Kohri, M.; Kobayashi, A.; Noguchi, M.; Kawaida, S.-i.; Watanabe, T.; Shoda, S.-i. (Holzforschung, 2006)

(untitled) - Crich, D.; Dudkin, V. (J. Am. Chem. Soc., 2001)

(untitled) - Kuyama, H.; Nakahara, Y.; Nukada, T.; Ito, Y.; Nakahara, Y.; Ogawa, T. (Carbohydr. Res., 1993)

(untitled) - Kanie, O.; Ito, Y.; Ogawa, T. (J. Am. Chem. Soc., 1994)

(untitled) - Yudina, O. N.; Tsvetkov, Y. E.; Nifantiev, N. E. (Russ. Chem. Bull., 2015)

(untitled) - Yudina, O. N.; Tsvetkov, Y. E.; Nifantiev, N. E. (Russ. Chem. Bull., 2016)

(untitled) - Kawada, T.; Yoneda, Y. (Monatsh. Chem., 2009)

(untitled) - Kawada, T.; Yoneda, Y. (Monatsh. Chem., 2009)

(untitled) - Bedini, E.; Cirillo, L.; Marchetti, R.; Basso, S.; Tufano, D.; Molinaro, A.; Parrilli, M. (Synlett, 2013)

(untitled) - Barroca-Aubry, N.; Pernet-Poil-Chevrier, A.; Domard, A.; Trombotto, S. (Carbohydr. Res., 2010)

(untitled) - Tyrikos‐Ergas, T.; Bordoni, V.; Fittolani, G.; Chaube, M. A.; Grafmüller, A.; Seeberger, P. H.; Delbianco, M. (Chem. – Eur. J., 2021)

(untitled) - Enugala, R.; Carvalho, L. C. R.; Dias Pires, M. J.; Marques, M. M. B. (Chem. – Asian J., 2012)

(untitled) - Yang, F.; Du, Y. (Carbohydr. Res., 2003)

(untitled) - Yamago, S.; Yamada, T.; Maruyama, T.; Yoshida, J.-i. (Angew. Chem., Int. Ed., 2004)

(untitled) - Gening, M. L.; Tsvetkov, Y. E.; Pier, G. B.; Nifantiev, N. E. (Carbohydr. Res., 2007)

(untitled) - Gening, M. L.; Titov, D. V.; Grachev, A. A.; Gerbst, A. G.; Yudina, O. N.; Shashkov, A. S.; Chizhov, A. O.; Tsvetkov, Y. E.; Nifantiev, N. E. (Eur. J. Org. Chem., 2010)

(untitled) - Nokami, T.; Hayashi, R.; Saigusa, Y.; Shimizu, A.; Liu, C.-Y.; Mong, K.-K. T.; Yoshida, J.-i. (Org. Lett., 2013)

(untitled) - Kröck, L.; Esposito, D.; Castagner, B.; Wang, C.-C.; Bindschädler, P.; Seeberger, P. H. (Chem. Sci., 2012)

(untitled) - Morando, M.; Yao, Y.; Martín-Santamaría, S.; Zhu, Z.; Xu, T.; Cañada, F. J.; Zhang, Y.; Jiménez-Barbero, J. (Chem. – Eur. J., 2010)

(untitled) - Hölemann, A.; Stocker, B. L.; Seeberger, P. H. (J. Org. Chem., 2006)

Advances in Carbohydrate Chemistry and Biochemistry - Cai, F.; Wu, B.; Crich, D. (Stereocontrolled Synthesis of Mannans and Rhamnans, 2009)

(untitled) - Cheon, H.-S.; Lian, Y.; Kishi, Y. (Org. Lett., 2007)

(untitled) - Li, X.; Li, C.; Liu, R.; Wang, J.; Wang, Z.; Chen, Y.; Yang, Y. (Org. Lett., 2019)

(untitled) - Jayaprakash, K. N.; Lu, J.; Fraser-Reid, B. (Angew. Chem., 2005)

(untitled) - Sawettanai, N.; Leelayuwapan, H.; Karoonuthaisiri, N.; Ruchirawat, S.; Boonyarattanakalin, S. (J. Org. Chem., 2019)

(untitled) - Leelayuwapan, H.; Kangwanrangsan, N.; Chawengkirttikul, R.; Ponpuak, M.; Charlermroj, R.; Boonyarattanakalin, K.; Ruchirawat, S.; Boonyarattanakalin, S. (J. Org. Chem., 2017)

(untitled) - Calin, O.; Eller, S.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2013)

(untitled) - Naresh, K.; Schumacher, F.; Hahm, H. S.; Seeberger, P. H. (Chem. Commun., 2017)

(untitled) - Joseph, A. A.; Pardo-Vargas, A.; Seeberger, P. H. (J. Am. Chem. Soc., 2020)

(untitled) - Yu, Y.; Kononov, A.; Delbianco, M.; Seeberger, P. H. (Chem. – Eur. J., 2018)

(untitled) - Sahloul, K.; Lowary, T. L. (J. Org. Chem., 2015)

(untitled) - Pardo-Vargas, A.; Bharate, P.; Delbianco, M.; Seeberger, P. H. (Beilstein J. Org. Chem., 2019)

(untitled) - van der Vorm, S.; Hansen, T.; van Hengst, J. M. A.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Chem. Soc. Rev., 2019)

(untitled) - Nicolardi, S.; Joseph, A. A.; Zhu, Q.; Shen, Z.; Pardo-Vargas, A.; Chiodo, F.; Molinaro, A.; Silipo, A.; van der Burgt, Y. E. M.; Yu, B.; Seeberger, P. H.; Wuhrer, M. (Anal. Chem. (Washington, DC, U. S.), 2021)

(untitled) - Sasaki, K.; Tohda, K. (Tetrahedron Lett., 2018)

(untitled) - Li, Q.; Levi, S. M.; Jacobsen, E. N. (J. Am. Chem. Soc., 2020)

(untitled) - Geng, X.; Wang, G.; Guo, Z.; Gu, G. (J. Org. Chem., 2020)

(untitled) - Crich, D. (Acc. Chem. Res., 2010)

(untitled) - Crich, D.; Sun, S. (Tetrahedron, 1998)

(untitled) - Crich, D.; Chandrasekera, N. S. (Angew. Chem., Int. Ed., 2004)

(untitled) - Crich, D.; Banerjee, A.; Yao, Q. (J. Am. Chem. Soc., 2004)

(untitled) - Crich, D.; Li, W.; Li, H. (J. Am. Chem. Soc., 2004)

(untitled) - Crich, D.; Li, H.; Yao, Q.; Wink, D. J.; Sommer, R. D.; Rheingold, A. L. (J. Am. Chem. Soc., 2001)

(untitled) - Codée, J. D. C.; Kröck, L.; Castagner, B.; Seeberger, P. H. (Chem. – Eur. J., 2008)

(untitled) - Ohara, K.; Lin, C.-C.; Yang, P.-J.; Hung, W.-T.; Yang, W.-B.; Cheng, T.-J. R.; Fang, J.-M.; Wong, C.-H. (J. Org. Chem., 2013)

(untitled) - Mathew, F.; Mach, M.; Hazen, K.; Fraser-Reid, B. (Synlett, 2003)

(untitled) - Nitz, M.; Purse, B. W.; Bundle, D. R. (Org. Lett., 2000)

(untitled) - Nitz, M.; Bundle, D. R. (J. Org. Chem., 2001)

(untitled) - van den Bos, L. J.; Dinkelaar, J.; Overkleeft, H. S.; van der Marel, G. A. (J. Am. Chem. Soc., 2006)

(untitled) - Codée, J. D. C.; van den Bos, L. J.; de Jong, A.-R.; Dinkelaar, J.; Lodder, G.; Overkleeft, H. S.; van der Marel, G. A. (J. Org. Chem., 2009)

(untitled) - Hansen, T.; Lebedel, L.; Remmerswaal, W. A.; van der Vorm, S.; Wander, D. P. A.; Somers, M.; Overkleeft, H. S.; Filippov, D. V.; Désiré, J.; Mingot, A.; Bleriot, Y.; van der Marel, G. A.; et al. (ACS Cent. Sci., 2019)

(untitled) - Dinkelaar, J.; de Jong, A. R.; van Meer, R.; Somers, M.; Lodder, G.; Overkleeft, H. S.; Codée, J. D. C.; van der Marel, G. A. (J. Org. Chem., 2009)

(untitled) - Walvoort, M. T. C.; van den Elst, H.; Plante, O. J.; Kröck, L.; Seeberger, P. H.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Angew. Chem., Int. Ed., 2012)

(untitled) - Pan, D.; Zhang, L.; Hua, Q.; Yang, Y. (Org. Biomol. Chem., 2019)

(untitled) - Tang, S.-L.; Pohl, N. L. B. (Org. Lett., 2015)

(untitled) - Jahn, M.; Stoll, D.; Warren, R. A. J.; Szabó, L.; Singh, P.; Gilbert, H. J.; Ducros, V. M.-A.; Davies, G. J.; Withers, S. G. (Chem. Commun., 2003)

(untitled) - Grimaud, F.; Pizzut-Serin, S.; Tarquis, L.; Ladevèze, S.; Morel, S.; Putaux, J.-L.; Potocki-Veronese, G. (Biomacromolecules, 2019)

(untitled) - Pawar, S. N.; Edgar, K. J. (Biomaterials, 2012)

(untitled) - Beswick, L.; Ahmadipour, S.; Dolan, J. P.; Rejzek, M.; Field, R. A.; Miller, G. J. (Carbohydr. Res., 2019)

(untitled) - Zhang, Q.; van Rijssel, E. R.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Eur. J. Org. Chem., 2016)

(untitled) - Dinkelaar, J.; van den Bos, L. J.; Hogendorf, W. F. J.; Lodder, G.; Overkleeft, H. S.; Codée, J. D. C.; van der Marel, G. A. (Chem. – Eur. J., 2008)

(untitled) - Zhang, Q.; van Rijssel, E. R.; Walvoort, M. T. C.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Giraud, M.-F.; Naismith, J. H. (Curr. Opin. Struct. Biol., 2000)

(untitled) - Geert Volbeda, A.; Reintjens, N. R. M.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Eur. J. Org. Chem., 2016)

(untitled) - Geert Volbeda, A.; van Mechelen, J.; Meeuwenoord, N.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (J. Org. Chem., 2017)

(untitled) - Tanaka, H.; Hamaya, Y.; Nishiwaki, N.; Ishida, H. (Carbohydr. Res., 2018)

(untitled) - Kohout, V. R.; Pohl, N. L. B. (Carbohydr. Res., 2019)

(untitled) - Zhang, J.; Kong, F. (Tetrahedron, 2003)

(untitled) - Palmacci, E. R.; Plante, O. J.; Hewitt, M. C.; Seeberger, P. H. (Helv. Chim. Acta, 2003)

(untitled) - Bedini, E.; Parrilli, M.; Unverzagt, C. (Tetrahedron Lett., 2002)

(untitled) - Bedini, E.; De Castro, C.; Erbs, G.; Mangoni, L.; Dow, J. M.; Newman, M.-A.; Parrilli, M.; Unverzagt, C. (J. Am. Chem. Soc., 2005)

(untitled) - Werz, D. B.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2005)

(untitled) - Govindarajan, M. (Carbohydr. Res., 2020)

(untitled) - Rai, D.; Kulkarni, S. S. (Org. Biomol. Chem., 2020)

(untitled) - Crich, D.; Bowers, A. A. (Org. Lett., 2006)

(untitled) - Zhu, Q.; Shen, Z.; Chiodo, F.; Nicolardi, S.; Molinaro, A.; Silipo, A.; Yu, B. (Nat. Commun., 2020)

(untitled) - Cai, J.; Hu, J.; Qin, C.; Li, L.; Shen, D.; Tian, G.; Zou, X.; Seeberger, P. H.; Yin, J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Yu, B. (Acc. Chem. Res., 2018)

(untitled) - Koeller, K. M.; Wong, C.-H. (Chem. Rev., 2000)

(untitled) - Pfrengle, F. (Curr. Opin. Chem. Biol., 2017)

Annual Plant Reviews - Nepogodiev, S. A.; Field, R. A.; Damager, I. (Approaches to Chemical Synthesis of Pectic Oligosaccharides, 2010)

(untitled) - Lichtenthaler, F. W.; Oberthür, M.; Peters, S. (Eur. J. Org. Chem., 2001)

(untitled) - Andersen, M. C. F.; Kračun, S. K.; Rydahl, M. G.; Willats, W. G. T.; Clausen, M. H. (Chem. – Eur. J., 2016)

(untitled) - Andersen, M. C. F.; Boos, I.; Kinnaert, C.; Awan, S. I.; Pedersen, H. L.; Kračun, S. K.; Lanz, G.; Rydahl, M. G.; Kjærulff, L.; Håkansson, M.; Kimbung, R.; Logan, D. T.; et al. (Org. Biomol. Chem., 2018)

(untitled) - Bartetzko, M. P.; Schuhmacher, F.; Seeberger, P. H.; Pfrengle, F. (J. Org. Chem., 2017)

(untitled) - Zeng, Y.; Li, A.; Kong, F. (Tetrahedron Lett., 2003)

(untitled) - Li, A.; Kong, F. (Carbohydr. Res., 2004)

(untitled) - Li, A.; Zeng, Y.; Kong, F. (Carbohydr. Res., 2004)

(untitled) - Li, A.; Kong, F. (Bioorg. Med. Chem., 2005)

(untitled) - Andersen, M. C. F.; Boos, I.; Ruprecht, C.; Willats, W. G. T.; Pfrengle, F.; Clausen, M. H. (J. Org. Chem., 2017)

(untitled) - Bartetzko, M. P.; Schuhmacher, F.; Hahm, H. S.; Seeberger, P. H.; Pfrengle, F. (Org. Lett., 2015)

(untitled) - Imamura, A.; Ando, H.; Korogi, S.; Tanabe, G.; Muraoka, O.; Ishida, H.; Kiso, M. (Tetrahedron Lett., 2003)

(untitled) - Imamura, A.; Matsuzawa, N.; Sakai, S.; Udagawa, T.; Nakashima, S.; Ando, H.; Ishida, H.; Kiso, M. (J. Org. Chem., 2016)

(untitled) - Kazakova, E. D.; Yashunsky, D. V.; Krylov, V. B.; Bouchara, J.-P.; Cornet, M.; Valsecchi, I.; Fontaine, T.; Latgé, J.-P.; Nifantiev, N. E. (J. Am. Chem. Soc., 2020)

(untitled) - Zhang, Y.; Gómez‐Redondo, M.; Jiménez‐Osés, G.; Arda, A.; Overkleeft, H. S.; Marel, G. A.; Jiménez‐Barbero, J.; Codée, J. D. C. (Angew. Chem., Int. Ed., 2020)

(untitled) - Nakahara, Y.; Ogawa, T. (Carbohydr. Res., 1989)

(untitled) - Nakahara, Y.; Ogawa, T. (Carbohydr. Res., 1990)

(untitled) - Clausen, M. H.; Madsen, R. (Chem. – Eur. J., 2003)

(untitled) - Clausen, M. H.; Jørgensen, M. R.; Thorsen, J.; Madsen, R. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - van den Bos, L. J.; Codée, J. D. C.; Litjens, R. E. J. N.; Dinkelaar, J.; Overkleeft, H. S.; van der Marel, G. A. (Eur. J. Org. Chem., 2007)

(untitled) - Justen, A. M.; Hodges, H. L.; Kim, L. M.; Sadecki, P. W.; Porfirio, S.; Ultee, E.; Black, I.; Chung, G. S.; Briegel, A.; Azadi, P.; Kiessling, L. L. (Sci. Adv., 2020)

(untitled) - King, J. D.; Berry, S.; Clarke, B. R.; Morris, R. J.; Whitfield, C. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - May, J. F.; Splain, R. A.; Brotschi, C.; Kiessling, L. L. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Wheatley, R. W.; Zheng, R. B.; Richards, M. R.; Lowary, T. L.; Ng, K. K. S. (J. Biol. Chem., 2012)

(untitled) - Savková, K.; Huszár, S.; Baráth, P.; Pakanová, Z.; Kozmon, S.; Vancová, M.; Tesařová, M.; Blaško, J.; Kaliňák, M.; Singh, V.; Korduláková, J.; Mikušová, K. (Proc. Natl. Acad. Sci. U. S. A., 2021)

(untitled) - Woodward, R.; Yi, W.; Li, L.; Zhao, G.; Eguchi, H.; Sridhar, P. R.; Guo, H.; Song, J. K.; Motari, E.; Cai, L.; Kelleher, P.; Liu, X.; et al. (Nat. Chem. Biol., 2010)

(untitled) - Peltier, P.; Euzen, R.; Daniellou, R.; Nugier-Chauvin, C.; Ferrières, V. (Carbohydr. Res., 2008)

(untitled) - Houseknecht, J. B.; Lowary, T. L. (Curr. Opin. Chem. Biol., 2001)

(untitled) - Completo, G. C.; Lowary, T. L. (J. Org. Chem., 2008)

(untitled) - Argunov, D. A.; Krylov, V. B.; Nifantiev, N. E. (Org. Lett., 2016)

(untitled) - Krylov, V. B.; Argunov, D. A.; Vinnitskiy, D. Z.; Verkhnyatskaya, S. A.; Gerbst, A. G.; Ustyuzhanina, N. E.; Dmitrenok, A. S.; Huebner, J.; Holst, O.; Siebert, H.-C.; Nifantiev, N. E. (Chem. – Eur. J., 2014)

(untitled) - Joe, M.; Lowary, T. L. (Can. J. Chem., 2016)

(untitled) - Sabbavarapu, N. M.; Seeberger, P. H. (J. Org. Chem., 2021)

(untitled) - Mourão, P. (Trends Cardiovasc. Med., 1999)

(untitled) - Berteau, O.; Mulloy, B. (Glycobiology, 2003)

(untitled) - Ustyuzhanina, N.; Krylov, V.; Grachev, A.; Gerbst, A.; Nifantiev, N. (Synthesis, 2006)

(untitled) - Arafuka, S.; Koshiba, N.; Takahashi, D.; Toshima, K. (Chem. Commun., 2014)

(untitled) - Liu, K.; Wang, L.; Guo, Z. (J. Carbohydr. Chem., 2019)

(untitled) - Mishra, B.; Manmode, S.; Panda, R. R. A.; Hotha, S. (Eur. J. Org. Chem., 2017)

(untitled) - Podvalnyy, N. M.; Abronina, P. I.; Zdorovenko, E. L.; Chizhov, A. O.; Zinin, A. I.; Torgov, V. I.; Kononov, L. O. (Russ. Chem. Bull., 2014)

(untitled) - Podvalnyy, N. M.; Chizhov, A. O.; Zinin, A. I.; Kononov, L. O. (Carbohydr. Res., 2016)

(untitled) - Leelayuwapan, H.; Ruchirawat, S.; Boonyarattanakalin, S. (Carbohydr. Polym., 2019)

(untitled) - Hori, M.; Nakatsubo, F. (Macromolecules, 2000)

(untitled) - Panova, M. V.; Podvalnyy, N. M.; Okun, E. L.; Abronina, P. I.; Chizhov, A. O.; Kononov, L. O. (Carbohydr. Res., 2018)

(untitled) - Lu, J.; Fraser-Reid, B. (Chem. Commun., 2005)

(untitled) - Fraser-Reid, B.; Lu, J.; Jayaprakash, K. N.; López, J. C. (Tetrahedron: Asymmetry, 2006)

(untitled) - Joe, M.; Bai, Y.; Nacario, R. C.; Lowary, T. L. (J. Am. Chem. Soc., 2007)

(untitled) - Ishiwata, A.; Ito, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Thadke, S. A.; Mishra, B.; Islam, M.; Pasari, S.; Manmode, S.; Rao, B. V.; Neralkar, M.; Shinde, G. P.; Walke, G.; Hotha, S. (Nat. Commun., 2017)

(untitled) - Islam, M.; Shinde, G. P.; Hotha, S. (Chem. Sci., 2017)

(untitled) - Pasari, S.; Manmode, S.; Walke, G.; Hotha, S. (Chem. – Eur. J., 2018)

(untitled) - Kandasamy, J.; Hurevich, M.; Seeberger, P. H. (Chem. Commun., 2013)

(untitled) - Du, Y.; Pan, Q.; Kong, F. (Synlett, 1999)

(untitled) - Du, Y.; Pan, Q.; Kong, F. (Carbohydr. Res., 2000)

(untitled) - Ishiwata, A.; Akao, H.; Ito, Y. (Org. Lett., 2006)

(untitled) - Wu, Y.; Xiong, D.-C.; Chen, S.-C.; Wang, Y.-S.; Ye, X.-S. (Nat. Commun., 2017)

(untitled) - Mende, M.; Bednarek, C.; Wawryszyn, M.; Sauter, P.; Biskup, M. B.; Schepers, U.; Bräse, S. (Chem. Rev., 2016)

(untitled) - Yu, M.; Zhang, T.; Zhang, W.; Sun, Q.; Li, H.; Li, J.-p. (Front. Mol. Biosci., 2021)

(untitled) - Zhang, Q.; Chen, C. Z.; Swaroop, M.; Xu, M.; Wang, L.; Lee, J.; Wang, A. Q.; Pradhan, M.; Hagen, N.; Chen, L.; Shen, M.; Luo, Z.; et al. (Cell Discovery, 2020)

(untitled) - Ricard-Blum, S.; Lisacek, F. (Glycoconjugate J., 2017)

(untitled) - Mattson, J. M.; Turcotte, R.; Zhang, Y. (Biomech. Model. Mechanobiol., 2017)

(untitled) - Badri, A.; Williams, A.; Linhardt, R. J.; Koffas, M. A. G. (Curr. Opin. Biotechnol., 2018)

(untitled) - Gama, C. I.; Tully, S. E.; Sotogaku, N.; Clark, P. M.; Rawat, M.; Vaidehi, N.; Goddard, W. A., III; Nishi, A.; Hsieh-Wilson, L. C. (Nat. Chem. Biol., 2006)

(untitled) - Habuchi, H.; Habuchi, O.; Kimata, K. (Glycoconjugate J., 2004)

(untitled) - Zhang, X.; Pagadala, V.; Jester, H. M.; Lim, A. M.; Pham, T. Q.; Goulas, A. M. P.; Liu, J.; Linhardt, R. J. (Chem. Sci., 2017)

(untitled) - Wang, Z.; Hsieh, P.-H.; Xu, Y.; Thieker, D.; Chai, E. J. E.; Xie, S.; Cooley, B.; Woods, R. J.; Chi, L.; Liu, J. (J. Am. Chem. Soc., 2017)

(untitled) - Arnold, K.; Liao, Y.-E.; Liu, J. (Biomedicines, 2020)

(untitled) - Lee, J.-C.; Lu, X.-A.; Kulkarni, S. S.; Wen, Y.-S.; Hung, S.-C. (J. Am. Chem. Soc., 2004)

(untitled) - Miller, R. L.; Guimond, S. E.; Schwörer, R.; Zubkova, O. V.; Tyler, P. C.; Xu, Y.; Liu, J.; Chopra, P.; Boons, G.-J.; Grabarics, M.; Manz, C.; Hofmann, J.; et al. (Nat. Commun., 2020)

(untitled) - Liu, J.; Linhardt, R. J. (Nat. Prod. Rep., 2014)

(untitled) - Hu, Y.-P.; Lin, S.-Y.; Huang, C.-Y.; Zulueta, M. M. L.; Liu, J.-Y.; Chang, W.; Hung, S.-C. (Nat. Chem., 2011)

(untitled) - Muñoz-García, J. C.; López-Prados, J.; Angulo, J.; Díaz-Contreras, I.; Reichardt, N.; de Paz, J. L.; Martín-Lomas, M.; Nieto, P. M. (Chem. – Eur. J., 2012)

(untitled) - Dai, X.; Liu, W.; Zhou, Q.; Cheng, C.; Yang, C.; Wang, S.; Zhang, M.; Tang, P.; Song, H.; Zhang, D.; Qin, Y. (J. Org. Chem., 2016)

(untitled) - Zong, C.; Venot, A.; Li, X.; Lu, W.; Xiao, W.; Wilkes, J.-S. L.; Salanga, C. L.; Handel, T. M.; Wang, L.; Wolfert, M. A.; Boons, G.-J. (J. Am. Chem. Soc., 2017)

(untitled) - Dey, S.; Wong, C.-H. (Chem. Sci., 2018)

(untitled) - Pawar, N. J.; Wang, L.; Higo, T.; Bhattacharya, C.; Kancharla, P. K.; Zhang, F.; Baryal, K.; Huo, C.-X.; Liu, J.; Linhardt, R. J.; Huang, X.; Hsieh‐Wilson, L. C. (Angew. Chem., Int. Ed., 2019)

(untitled) - Hansen, S. U.; Baráth, M.; Salameh, B. A. B.; Pritchard, R. G.; Stimpson, W. T.; Gardiner, J. M.; Jayson, G. C. (Org. Lett., 2009)

(untitled) - Hansen, S. U.; Miller, G. J.; Jayson, G. C.; Gardiner, J. M. (Org. Lett., 2013)

(untitled) - Hansen, S. U.; Miller, G. J.; Cole, C.; Rushton, G.; Avizienyte, E.; Jayson, G. C.; Gardiner, J. M. (Nat. Commun., 2013)

(untitled) - Hansen, S. U.; Miller, G. J.; Cliff, M. J.; Jayson, G. C.; Gardiner, J. M. (Chem. Sci., 2015)

(untitled) - Zhang, X.; Lin, L.; Huang, H.; Linhardt, R. J. (Acc. Chem. Res., 2020)

(untitled) - Xu, Y.; Masuko, S.; Takieddin, M.; Xu, H.; Liu, R.; Jing, J.; Mousa, S. A.; Linhardt, R. J.; Liu, J. (Science, 2011)

(untitled) - Xu, Y.; Cai, C.; Chandarajoti, K.; Hsieh, P.-H.; Li, L.; Pham, T. Q.; Sparkenbaugh, E. M.; Sheng, J.; Key, N. S.; Pawlinski, R.; Harris, E. N.; Linhardt, R. J.; et al. (Nat. Chem. Biol., 2014)

(untitled) - Zong, C.; Venot, A.; Dhamale, O.; Boons, G.-J. (Org. Lett., 2013)

(untitled) - Masuko, S.; Bera, S.; Green, D. E.; Weïwer, M.; Liu, J.; DeAngelis, P. L.; Linhardt, R. J. (J. Org. Chem., 2012)

(untitled) - Weïwer, M.; Sherwood, T.; Green, D. E.; Chen, M.; DeAngelis, P. L.; Liu, J.; Linhardt, R. J. (J. Org. Chem., 2008)

(untitled) - Li, J.-p.; Hagner-McWhirter, Å.; Kjellén, L.; Palgi, J.; Jalkanen, M.; Lindahl, U. (J. Biol. Chem., 1997)

(untitled) - Sheng, J.; Xu, Y.; Dulaney, S. B.; Huang, X.; Liu, J. (J. Biol. Chem., 2012)

(untitled) - Xu, Y.; Pempe, E. H.; Liu, J. (J. Biol. Chem., 2012)

(untitled) - Lu, W.; Zong, C.; Chopra, P.; Pepi, L. E.; Xu, Y.; Amster, I. J.; Liu, J.; Boons, G.-J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Yamada, S.; Sugahara, K. (Curr. Drug Discovery Technol., 2008)

(untitled) - Ramadan, S.; Li, T.; Yang, W.; Zhang, J.; Rashidijahanabad, Z.; Tan, Z.; Parameswaran, N.; Huang, X. (ACS Cent. Sci., 2020)

(untitled) - Li, J.; Su, G.; Liu, J. (Angew. Chem., Int. Ed., 2017)

(untitled) - Sugiura, N.; Shimokata, S.; Minamisawa, T.; Hirabayashi, J.; Kimata, K.; Watanabe, H. (Glycoconjugate J., 2008)

(untitled) - Köwitsch, A.; Zhou, G.; Groth, T. (J. Tissue Eng. Regener. Med., 2018)

(untitled) - Lu, X.; Kamat, M. N.; Huang, L.; Huang, X. (J. Org. Chem., 2009)

(untitled) - Walvoort, M. T. C.; Volbeda, A. G.; Reintjens, N. R. M.; van den Elst, H.; Plante, O. J.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Org. Lett., 2012)

(untitled) - Fu, X.; Shang, W.; Wang, S.; Liu, Y.; Qu, J.; Chen, X.; Wang, P. G.; Fang, J. (Chem. Commun., 2017)

(untitled) - Wang, Y.; Li, S.; Xu, X.; Tan, Y.; Liu, X.-w.; Fang, J. (Carbohydr. Polym., 2020)

(untitled) - Pomin, V. H. (Int. J. Biol. Macromol., 2015)

(untitled) - Ohmae, M.; Yamazaki, Y.; Sezukuri, K.; Takada, J. (Trends Glycosci. Glycotechnol., 2019)

(untitled) - Ohmae, M.; Sakaguchi, K.; Kaneto, T.; Fujikawa, S.-i.; Kobayashi, S. (ChemBioChem, 2007)

(untitled) - Hahm, H. S.; Broecker, F.; Kawasaki, F.; Mietzsch, M.; Heilbronn, R.; Fukuda, M.; Seeberger, P. H. (Chem, 2017)

(untitled) - Kobayashi, Y.; Horie, Y.; Honjo, K.; Uemura, T.; Kitagawa, S. (Chem. Commun., 2016)

(untitled) - Holerca, M. N.; Peterca, M.; Partridge, B. E.; Xiao, Q.; Lligadas, G.; Monteiro, M. J.; Percec, V. (J. Am. Chem. Soc., 2020)

(untitled) - Begum, S.; Hassan, Z.; Bräse, S.; Tsotsalas, M. (Langmuir, 2020)

(untitled) - Dawson, P. E.; Kent, S. B. H. (Annu. Rev. Biochem., 2000)

(untitled) - Kuir, D.; Guillemineau, M.; Auzanneau, F.-I. (J. Org. Chem., 2015)

(untitled) - Lassfolk, R.; Rahkila, J.; Johansson, M. P.; Ekholm, F. S.; Wärnå, J.; Leino, R. (J. Am. Chem. Soc., 2019)

(untitled) - Asano, S.; Tanaka, H.-N.; Imamura, A.; Ishida, H.; Ando, H. (Org. Lett., 2019)

(untitled) - El Seoud, O. A.; Koschella, A.; Fidale, L. C.; Dorn, S.; Heinze, T. (Biomacromolecules, 2007)

(untitled) - Shi, X.; Huang, Y.; Mao, Y.; Naimy, H.; Zaia, J. (J. Am. Soc. Mass Spectrom., 2012)

(untitled) - Solleder, S. C.; Schneider, R. V.; Wetzel, K. S.; Boukis, A. C.; Meier, M. A. R. (Macromol. Rapid Commun., 2017)

(untitled) - Aksakal, R.; Mertens, C.; Soete, M.; Badi, N.; Du Prez, F. (Adv. Sci., 2021)

(untitled) - Martens, S.; Van den Begin, J.; Madder, A.; Du Prez, F. E.; Espeel, P. (J. Am. Chem. Soc., 2016)

(untitled) - Al Ouahabi, A.; Charles, L.; Lutz, J.-F. (J. Am. Chem. Soc., 2015)

(untitled) - Genabeek, B.; Lamers, B. A. G.; Hawker, C. J.; Meijer, E. W.; Gutekunst, W. R.; Schmidt, B. V. K. J. (J. Polym. Sci. (Hoboken, NJ, U. S.), 2021)

(untitled) - Govindaraju, T.; Avinash, M. B. (Nanoscale, 2012)